Carney Complex - Kamilaris, Crystal D. C.; Faucz, Fabio Rueda; Voutetakis, Antonis; Stratakis, Constantine A. (Experimental and Clinical Endocrinology & Diabetes, 2019)
Carney complex is a rare, autosomal dominant, multiple endocrine neoplasia and lentiginosis syndrome, caused in most patients by defects in the PRKAR1A gene, which encodes the regulatory subunit type 1α of protein kinase A. Inactivating defects of PRKAR1A lead to aberrant cyclic-AMP-protein kinase A signaling. Patients may develop multiple skin abnormalities and a variety of endocrine and non-endocrine tumors. Endocrine manifestations include primary pigmented nodular adrenocortical disease, that may cause Cushing syndrome, growth-hormone secreting pituitary adenoma or pituitary somatotropic hyperplasia which can result in acromegaly, as well as gonadal and thyroid tumors. Non-endocrine tumors associated with Carney complex include myxomas of the heart, breast, and other sites, psamommatous melanotic schwannomas, breast ductal adenomas, osteochondromyxomas, and a predisposition to a number of malignancies from adrenal to pancreatic and liver cancer.
Keywords: Carney complex; PRKAR1A; primary pigmented nodular adrenocortical disease; myxomas; acromegaly; lentigines